Tanggung Jawab Kurator dalam Penjualan Harta Pailit di Bawah Harga Pasar - Moch Zulkarnain Al Mufti (Universitas Islam Indonesia, 2016)
This research aims to identify the responsibility of the curator in selling the acquired properties under the market price. Though the curator in the management handling and the accomplishment of the acquired properties is quite high, the curator in running the task does not mean to be free to do anything. A curator can be asked for his or her responsibility personally if he or she has made the loss towards the acquired properties. The problem formulation in this research is how the responsibility of a curator is in terms of the sale of acquired properties under the market price. This is a normative legal research and the results of the research concluded that the responsibility of the curator in doing the management handling and accomplishment of the acquired properties basically has been regulated in the Article of 72 Law No. 37 of 2004 on bankruptcy and the postpone of the obligation to pay the loan. However, until today, there is no any certainty about the limitation of the mistake and dereliction. Keywords: Curator, responsibility, acquired property